The Porosity Effect of Stainless Steel Balls on Forced Convection Pipe Flow - Flayh, Ayser Munner; Ghashim, Sajida Lafta (Al-Nahrain Journal for Engineering Sciences, 2019)
An experimental study has been carried out to investigate the effects of stainless-steel balls on forced convection flow in pipe under uniform heat flux. Water is used as the working fluid and stainless-steel balls as a porous media. The Reynolds number range from (5000 to 9000) based on the diameter of the pipe. The experiments were conducted on three various numbers of stainless-steel balls (N) with various diameters (dp), which give various porosity (0.33, 0.38 and 0.41). These are (N= 2400, dp=1mm), (N=1600, dp=3mm) and (N= 750, dp=5mm). Results show that, heat transfer coefficient increases with the decrease in the porosity due to the reduction in the space between balls. This led to an increase in turbulence and produced eddies. Furthermore, enhancement in heat transfer coefficient reached its maximum value of (45%) for ball diameter with (dp=1mm) and water flow rate (9 L/min). New Correlation equations for the average heat transfer coefficient were obtained for three different diameters of balls (1, 3 and 5 mm).